Epoxide ring-opening reaction by using sol-gel-synthesized palladium supported on a strontium hydroxyl fluoride catalyst - Acham, Vaibhav R.; Dongare, Mohan K.; Kemnitz, Erhard; Umbarkar, Shubhangi B. (Comptes Rendus Chimie, 2016)
Palladium supported on a strontium hydroxyl fluoride catalyst was synthesized by a one-pot fluorolytic sol-gel method. The prepared catalyst was characterized by various physicochemical techniques. The sol-gel method has led to the formation of a high surface area (57 m(2)g(-1)), mesoporous (pore diameter = 13.0 nm) catalyst with uniform dispersion of Pd nanoparticles of size similar to 7 nm on the surface of strontium hydroxyl fluoride. The catalyst was used for epoxide alcoholysis, and 100% conversion was obtained with 96% selectivity for beta-alkoxy alcohols under mild conditions: The catalyst could be recycled for up to three catalytic cycles without any appreciable decrease in conversion and selectivity, indicating the stability of the catalyst under the reaction conditions. Further, the mechanism of alcoholysis was proposed on the basis of the physicochemical characteristics of the catalyst and on the basis of the products formed during the catalytic reaction. (C) 2016 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.